Pinus oocarpa Shiede site index of forest plantations in Michoacán, Mexico - García-Cuevas, Xavier; RAUL ENRIQUE,; Jonathan,; Hiara,; Adrian,; Sáenz-Reyes, José Trinidad (Ecosistemas y Recursos Agropecuarios, 2024)
The dominant height of the trees in a site is an indirect indicator of the productivity of forest soils is called station quality, which is measured through the site index. The aim of this study was to fit Ad models as a function of age with a mixed effects modeling approach to generate site index curves in forest plantations of Pinus oocarpa Shiede in Ario de Rosales, Michoacán, Mexico. With 1 773 pairs of forest plantation dominant height-age data from two to 20 years old and 56 years old relicts, five growth models were fitted to choose a base model. The Weibull model was fitted by mixed effects modeling with the plot as an additive covariate in the site-related parameter. The dominant height guide curve and the polymorphic curves adequately cover the sample variability of the information and reliably represent the productivity of the site where these plantations grow. The bias and validation of the results showed reliability in the estimates. The technical shift in dominant height is between 5 and 15 years according to the quality of the season. With these results, it is possible to classify Pinus oocarpa forest plantations reliably and according to the level of productivity of each establishment site.
Keywords: Productivity; models; mixed effects; anamorphic; polymorphic